2014
DOI: 10.1016/j.rssm.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Class mobility across three generations in the U.S. and Germany

Abstract: Based on data from the Panel Study of Income Dynamics and the Socio-economic Panel, we study the class mobility of three concurrent generations in the U.S. and Germany. We find that, in both countries, the grandfathers' class is directly associated with their grandchildren's social position. We propose three possible mechanisms which could explain the observed multigenerational mobility patterns. First, we consider the role of class-specific resources for mobility strategies. Second, we suggest a more general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 41 publications
(51 reference statements)
4
66
0
Order By: Relevance
“…Similar results are also implied by analyses of rare surnames, where a strong persistence of (high) socioeconomic status in England, Sweden, United States, and other countries over several generations can be observed (Clark 2014). Hertel and Groh-Samberg (2014) compare Germany and the United States, examining class outcomes across three generations measured by a four-class version of the EGP scheme (Erikson, Goldthorpe and Portocarero 1979). For both countries they find significant three-generational associations in relative mobility.…”
Section: Introductionmentioning
confidence: 96%
“…Similar results are also implied by analyses of rare surnames, where a strong persistence of (high) socioeconomic status in England, Sweden, United States, and other countries over several generations can be observed (Clark 2014). Hertel and Groh-Samberg (2014) compare Germany and the United States, examining class outcomes across three generations measured by a four-class version of the EGP scheme (Erikson, Goldthorpe and Portocarero 1979). For both countries they find significant three-generational associations in relative mobility.…”
Section: Introductionmentioning
confidence: 96%
“…Even more strikingly, Jaeger (2012), Pfeffer (2014), Hertel and Groh-Samberg (2014) as well as Wightman and Danziger (2014) all agree that grandparent effects are not uniform across social strata and that net grandparent effects are in fact present in the tails of the (parental or grandparental) status distribution. Consistent with a theory of compensating resources, Jaeger (2012) and Wightman and Danziger (2014) report net grandparent effects on educational attainment among respondents from low-socioeconomic status (SES) households.…”
Section: Ziefle Persistent Educational Advantagementioning
confidence: 98%
“…Using the Panel Study of Income Dynamics (PSID) and the National Longitudinal Survey of Youth (NLSY) data instead of the Wisconsin Longitudinal Survey (WLS) that Warren and Hauser (1997) had relied upon, Jaeger (2012) as well as Wightman and Danziger (2014) confirm Warren and Hauser's (1997) core conclusion about the absence of net grandparent effects on children's attainment, whereas both Pfeffer (2014) and Hertel and Groh-Samberg (2014) report net grandparent effects on both educational attainment and respondents' class position. Even more strikingly, Jaeger (2012), Pfeffer (2014), Hertel and Groh-Samberg (2014) as well as Wightman and Danziger (2014) all agree that grandparent effects are not uniform across social strata and that net grandparent effects are in fact present in the tails of the (parental or grandparental) status distribution.…”
Section: Ziefle Persistent Educational Advantagementioning
confidence: 99%
“…In addition, analyses focusing on countries such as Sweden, Germany and the United States have noted the intergenerational transmission between grandparents and grandchildren. They have indicated that the lack of social mobility not only occurs between two consecutive cohorts, but also extends over time (Hällsten 2014 Hertel andGroh-Samberg 2014). Also in the case of Sweden, other studies have identified that children living with their parents in poor neighbourhoods were more likely to live in this type of neighbourhood in their adult stage.…”
Section: Intergenerational Transmission Of Achievementsmentioning
confidence: 99%